Superior subconjunctival dislocation of intraocular lens following blunt trauma: A rare case report - Gupta, Sharad; Yadav, Reena; Shrestha, Satbodh; Bista, Bipin; Gupta, Vidisa; Chaudhary, Sushma (Journal of Kathmandu Medical College, 2021)
Subconjunctival dislocation of the intraocular lens secondary to trauma is an unusual and serious condition in the pseudophakic eye. Here, a case of 75 years old male who had traumatic superior subconjunctival dislocation of intraocular lens to his right eye with cow’s horn is reported. The patient was managed with surgical extraction of the lens and planned for secondary intraocular lens implantation. It is quite challenging to manage such a case. Despite, proper surgical management visual outcomes are always guarded in such patients with blunt trauma.